Application of glycemic qualification rate based on fingerstick glucose monitoring in women with gestational diabetes mellitus. (31st December 2023) - Zeng, Rui; Cao, Xiaopei; Chen, Nan; Pei, Ling; Xu, Changliu; Wang, Chenxue; Liu, Huiling; Deng, Wanping; Li, Yanbing
Abstract: Objective: To explore the appropriate application of glycemic qualification rate (GQR) calculated by fingerstick blood glucose (BG) monitoring for patients with gestational diabetes mellitus (GDM) by analyzing the relationship between BG control and adverse pregnancy outcomes. Methods: Fingerstick Blood Glucose data during the second and third trimester of singleton pregnant women diagnosed with GDM were collected. GQR which is defined as the percentage of fingerstick BG values reaching the targets of BG control in a period of time was calculated. Patients were divided into three groups according to tertiles (tertile 1, GQR <56.25%; tertile 2, GQR 56.25–75%; and tertile 3, GQR ≥75%). Pregnant outcomes were compared among the three groups. Univariate analysis and logistic regression were performed to analyze the potential relationship between GQR and pregnancy outcomes. Receiver operating characteristic (ROC) curves were calculated to determine the cutoff values. We also explored that whether twice or three times monitoring per day would be adequate for GQR calculation, so we brought in two or three glucose measuring times per day to explore the relationship between new GQR and adverse outcomes. Results: A total of 311 patients diagnosed with GDM were analyzed. In univariate analysis, the incidences of cesarean section of tertile 1–3 groups were 61.4%, 58.7%, and 44.9%, respectively ( p  < .05). The incidences of neonatal hypoglycemia of tertiles 1–3 groups were 19.8%, 18.6%, and 8.7% ( p  < .05). The difference of composite outcomes was statistically significant ( p  = .001). After adjustment, the patients with worse BG control (lower GQR) had higher risk of cesarean section (tertile 1 – aOR = 2.029, 1.128–3.648), neonatal hypoglycemia (tertile 1: aOR = 2.498, 1.082–5.766) as well as composite outcomes. The ROC curve of GQR indicated the predictive value for neonatal hypoglycemia (area under the ROC curve (AUC) 0.612 (0.532–0.692)) and neonatal composite outcomes (AUC 0.593 (0.528–0.657)) with optimal cutoff values of 81.1% and 73.5%, respectively. We also explored that whether twice or three times monitoring per day would be adequate for GQR calculation. The result showed that GQR only calculated by FBG + 2hPG after lunch (2h AL) per day also had well relationship with cesarean section (tertile 1: OR = 2.412, 1.322–4.398), neonatal hypoglycemia (tertile 1: aOR = 4.497, 1.607–12.586), and neonatal composite outcomes (tertile 1: aOR = 1.959, 95% confidence interval (CI): 1.114–3.444, p  = .020). Conclusions: The GQR calculated by the easily applicable fingerstick BG is related to occurrence of cesarean section and neonatal hypoglycemia in GDM women. GQR ≥ 80% is recommended for better pregnancy outcomes. As for the number of points monitoring per day, GQR calculated by FBG + 2h AL was an optimal option for better pregnancy outcomes if mothers needed to simplify the process of monitoring.